Burden of NASH related liver cancer from 1990 to 2021 at the global, regional, and national levels - Li, Shuang; Li, Shuangjiang; Guan, Linjing; Li, Mingjuan; Zhao, Jiahui; Wu, Min; Li, Qiuyun; Li, Hui; Ouyang, Guoqing; Pan, Guangdong (Frontiers in Nutrition, 2025)
BackgroundThe global burden of non-alcoholic steatohepatitis (NASH)-related liver cancer (NRLC) is increasing, making NASH the fastest-growing cause of liver cancer worldwide. This study presents a comprehensive analysis of NRLC burden at the global, regional, and national levels, further categorized by age, sex, and sociodemographic index (SDI).MethodData on NRLC from the Global Burden of Disease, Injuries, and Risk Factors (GBD) study 2021 were downloaded at global, regional, and national levels. The numbers and age-standardized rates (ASRs) of incidence, mortality, and disability-adjusted life years (DALYs) were analyzed to quantify the global burden of NRLC. Additionally, percentage changes in ASRs were used to identify trends in NRLC from 1990 to 2021.ResultsGlobally, both the number of cases and ASRs for NRLC increased between 1990 and 2021. In 2021, there were 42,291 new cases, 40,925 deaths, and 995,475 DALYs attributed to NRLC. East Asia, South Asia, and Southeast Asia reported the highest absolute case numbers, while Western, Southern, and Eastern Sub-Saharan Africa exhibited the highest ASRs. From 1990 to 2021, Australasia, Southern Latin America, and High-income North America showed the most significant increases in NRLC incidence. Nationally, Mongolia, Gambia, and Mozambique exhibited the highest ASR in 2021.The greatest percentage increases in ASIR occurred in Australia, the United Kingdom, and New Zealand between 1990 and 2021. NRLC incidence rates were higher in men and increased with age, peaking at 80–89 years. Similar patterns were observed for NRLC-related deaths and DALYs. Regionally, ASRs initially declined but then increased as SDI rose. At the national level, ASRs consistently decreased with higher SDI.ConclusionThis study highlights the substantial burden of NRLC at global, regional, and national levels. Males and older individuals bear a higher disease burden, and considerable variation exists across different regions and countries. These findings provide critical insights for formulating effective strategies to prevent and manage NRLC.